1996
DOI: 10.1111/j.1600-0676.1996.tb00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hepatitis C virus RNA in the liver and its relation to histopathological changes

Abstract: To investigate a cellular mode of HCV‐infection in the liver and its pathological implications in relation to histopathological changes or clinical data, we studied the distribution of HCV‐RNA in the livers of 21 patients with HCV‐related chronic liver disease (chronic active hepatitis, 14 cases; cirrhosis, 7 cases) using the in situ hybridization technique. In situ hybridization was performed on 4% paraformaldehyde‐fixed frozen sections with digoxigenin‐labeled DNA probe deduced from the core region of HC–J4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In a previous paper, (Biagini et al, 2001), we emphasize the lack of clear correlation between HCV RNA molecular detection methods in biologic samples of patients with chronic hepatitis C, thus confirming the literature data (Akyol et al, 1992;Bresters et al, 1994;Negro and Hadengue, 1997;Scheuer et al, 1997;Dries et al, 1999;Chang et al, 2000). Moreover, our findings based on in situ RT-PCR approach revealed a nuclear detection of HCV RNA as previously described by several authors (Haruna et al, 1993;Nouri-Aria et al, 1993;Cho et al, 1996;Walker et al, 1998), but in discrepancy with others studies showing a cytoplas- mic localization (Tanaka et al, 1993;Tang et al, 1995;Kojima et al, 1996;Lau et al, 1996;Sansonno et al, 1996;Sansonno et al, 1997;Bettinger et al, 1999;Ohishi et al, 1999;Chang et al, 2000;Rodriguez-Inigo et al, 2000).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In a previous paper, (Biagini et al, 2001), we emphasize the lack of clear correlation between HCV RNA molecular detection methods in biologic samples of patients with chronic hepatitis C, thus confirming the literature data (Akyol et al, 1992;Bresters et al, 1994;Negro and Hadengue, 1997;Scheuer et al, 1997;Dries et al, 1999;Chang et al, 2000). Moreover, our findings based on in situ RT-PCR approach revealed a nuclear detection of HCV RNA as previously described by several authors (Haruna et al, 1993;Nouri-Aria et al, 1993;Cho et al, 1996;Walker et al, 1998), but in discrepancy with others studies showing a cytoplas- mic localization (Tanaka et al, 1993;Tang et al, 1995;Kojima et al, 1996;Lau et al, 1996;Sansonno et al, 1996;Sansonno et al, 1997;Bettinger et al, 1999;Ohishi et al, 1999;Chang et al, 2000;Rodriguez-Inigo et al, 2000).…”
Section: Discussionsupporting
confidence: 77%
“…everal studies based on the detection of hepatitis C virus (HCV) RNA or virus-related proteins in formaldehyde-fixed paraffin-embedded liver biopsies have been already reported. These studies used reverse transcriptase-polymerase chain reaction (RT-PCR) performed on extracted RNA (Guerrero et al, 1997;Svoboda-Newman et al, 1997;Dries et al, 1999;Soguero et al, 2000), in situ hybridization (Haruna et al, 1993;Nouri-Aria et al, 1993;Tang et al, 1995;Cho et al, 1996;Felgar et al, 1996;Kojima et al, 1996;Sansonno et al, 1996;Sansonno et al, 1997;Ohishi et al, 1999;Chang et al, 2000;Rodriguez-Inigo et al, 2000), in situ RT-PCR (Lidonnici et al, 1995;Nuovo, 1998;Walker et al, 1998;Biagini et al, 2001) and immunohistochemistry (IMH) (Gonzalez-Peralta et al, 1994;Komminoth et al, 1994;Chamlian et al, 1996;Vartanian et al, 1996;Kawamura et al, 1997;Moriya et al, 1997;Muramarsu et al, 1997;Brody et al, 1998;Yasui et al, 1998;Errington et al, 1999;Gomez et al, 1999;Kim et al, 1999;Nakopoulo et al, 1999;Nayak and Sathar, 1999;Wölk et al, 2000). Analysis of the corresponding data concerning the intracellular localization of HCV RNA and proteins revealed controversial results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors attributed this to the ultimate increase in ALT during the natural course of the disease [14]. While others suggested that ALT levels are released by direct virus-related cytopathic activity and/or by an immune-mediated process that is less activated in patients with PNALT [15]. Less likely, the clinical outcome of HCV infection can be influenced by the HCV genotype and/or to a lower degree of viral replication [16].…”
Section: Discussionmentioning
confidence: 99%